Electric Parameter Measurement on Main Generator Based on IoT for Safe Operational Feasibility - Herlambang, Sri Mulyanto; dwi santoso, Agus; Cirillo, Stefano; Harianto, Bambang Bagus (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The generator is the main source of electricity in the ship that will drive all activities on the ship. With the source of electricity supplied by the generator, human work will become lighter because it is helped by electrical energy. In order for the generator to work properly, it requires maintenance and must always be well controlled, so that the parameters generated by the generator must always be maintained by monitoring these parameters automatically using an ESP32 microcontroller. The parameters measured are current, voltage, power, frequency, work factor, KWh, RPM, temperature and vibration. By measuring the magnitude of these parameters can later be utilised as variables for maintenance and repair of the generator. The sensor used to measure the electrical parameters is the PZEM 004t module because it can measure all electrical quantities of the generator, while the temperature uses a DS18B20 sensor and vibration uses a SW-420 sensor module. Then to measure RPM using a potentiometer. The measurement results are displayed on the smartphone screen on the platform using Internet of Things (IoT) technology sent from the engine room.